Pain and/or Discomfort During Debracketing: A Review - Selma Elekdağ Türk (Galenos Yayinevi, 2019)
The topic of bracket removal and enamel integrity has been extensively investigated. Nevertheless, bracket removal, as far as pain and/or discomfort are concerned, is poorly delineated in the orthodontic literature, i.e., the scarcity of reports in this area is conspicuous. In fact, only six studies were retrieved upon a PubMed search. These clinical studies performed with metal brackets are presented in a chronological order in the present review. Pain and/or discomfort during bracket removal are urgently in need of additional studies. The orthodontists have to be well-informed and updated to convey all the aspects of this procedure to the patient.